2015
DOI: 10.1007/s10803-015-2468-8
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Area and Brain Volume in Autism Spectrum Disorder: Quantitative Analysis of Structural MRI from the ABIDE Database

Abstract: Reduced corpus callosum area and increased brain volume are two commonly reported findings in autism spectrum disorder (ASD). We investigated these two correlates in ASD and healthy controls using T1-weighted MRI scans from the Autism Brain Imaging Data Exchange (ABIDE). Automated methods were used to segment the corpus callosum and intracranial region. No difference in the corpus callosum area was found between ASD participants and healthy controls (ASD 598.53 ± 109 mm(2); control 596.82 ± 102 mm(2); p = 0.76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Prior evidence suggests a genetic effect of disease liability on ICV in these three disorders(2, 65, 66). In particular, reduced total brain gray matter volume was observed among unaffected relatives of individuals with schizophrenia(6769) and ADHD(65).…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence suggests a genetic effect of disease liability on ICV in these three disorders(2, 65, 66). In particular, reduced total brain gray matter volume was observed among unaffected relatives of individuals with schizophrenia(6769) and ADHD(65).…”
Section: Discussionmentioning
confidence: 99%
“…T1-weighted scans from all contributing ABIDE sites were rated for movement artifacts on a scale from 1 (worst quality) to 5 (best quality) by a reviewer blind to group status. The QA ratings may be downloaded from the following site: https://sites.google.com/site/hpardoe/cc_abide ( KucharskyHiess et al, 2015 ). Only scans that received the highest rating (i.e., 4 or 5) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Of the reviewed studies outlined in Supplementary Table 7, the most common finding for patients with autism was reduced corpus callosum volume (CCV) (Elnakib et al, 2011; Frazier and Hardan, 2009; Haar et al, 2016). Large studies utilising the ABIDE dataset obtained mixed results, with two studies reporting reduced regional CCV (Haar et al, 2016; Katuwal et al, 2016b) and another two studies reporting no difference in CCV (Kucharsky Hiess et al, 2015; Lefebvre et al, 2015), despite all studies using similar methods (FreeSurfer or atlas‐based segmentations of the CC). Reduced CCV was also found to be consistent in children (Nordahl et al, 2015), with CCV found to be associated with intelligence quotient (IQ) (Fredo et al, 2014).…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 99%